The Effect of Animation Book–Based Education on Adolescents’ Knowledge and Attitudes Toward Diabetes Mellitus Prevention: A Quasi-Experimental Study at Muhammadiyah 1 Junior High School, Sidoarjo, Indonesia - Bilqis Nikma Fauzan; Anita Joeliantina; Sari Luthfiyah; Moch Bahrudin (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
The increasing prevalence of diabetes mellitus (DM) among adolescents represents a significant public health challenge, largely driven by lifestyle factors and insufficient awareness of preventive measures during early life stages. Despite existing health education efforts, traditional media such as leaflets often fail to effectively engage this population, limiting their impact on knowledge and behavioral change. This study aimed to evaluate the effectiveness of animation book-based health education compared to conventional leaflet methods in enhancing knowledge and attitudes toward diabetes mellitus prevention among adolescents at Muhammadiyah 1 Junior High School, Sidoarjo, Indonesia. Utilizing a quasi-experimental design with non-equivalent control groups, 64 ninth-grade students were allocated evenly into an intervention group receiving animation book education and a control group receiving leaflet-based education. Pretest and posttest assessments were conducted using structured questionnaires to measure changes in knowledge and attitudes. Statistical analysis applying paired and independent t-tests revealed a significant improvement in both knowledge and positive attitudes in the intervention group compared to the control group (p = 0.001). Notably, the animation book group demonstrated a substantial increase in knowledge scores, with the percentage of students exhibiting “good” knowledge rising from 40.6% to 93.8%, while the control group showed only marginal gains. Attitudinal improvements followed a similar pattern, indicating that the animation book medium facilitates more effective cognitive and affective engagement. These findings suggest that animation book-based education serves as a superior and innovative pedagogical tool for school-based health promotion aimed at early diabetes prevention. Integration of such interactive media can enhance adolescent health literacy and support preventive behaviors, ultimately reducing the future burden of non-communicable diseases.